Extent and structure of genetic diversity in a collection of the tropical multipurpose shrub legume Cratylia argentea (Desv.) O. kuntze as revealed by RAPD markers - Andersson, Meike S.; Schultze-Kraft, Rainer; Peters, Michael; Duque E., Myriam Cristina; Gallego Sánchez, Gerardo J. (Elsevier, 2007)
The tropical multipurpose shrub legume Cratylia argentea is well adapted to acid soils of low to medium fertility and has excellent drought-tolerance. Due to its high nutritive value it is particularly suited as forage for dry-season supplementation. A collection of 47 C. argentea accessions in a collection, derived from seed replicating of original accessions with differing geographic origin and morphological and agronomic characteristics was investigated using molecular markers (RAPD (random amplified polymorphic DNA)). Genetic diversity (HT = 0.145) in the collection was low, with 30% of differentiation among groups and high genetic similarity among accessions (GS = 0.805). Within-accession variability was high. One taxonomic mismatch and five possible duplicate accessions were identified. Our results suggest that the genetic diversity in the C. argentea accessions studied is relatively homogeneously distributed, indicating the likelihood of extensive outcrossing. The genetic diversity of original accessions should be assessed to determine if outcrossing has occurred during or before ex situ storage. This might also support any decision on whether accessions should be bulked rather than maintaining them individually.